2013
DOI: 10.5194/cp-9-1985-2013
|View full text |Cite
|
Sign up to set email alerts
|

Droughts in the Czech Lands, 1090–2012 AD

Abstract: This paper addresses droughts in the Czech Lands in the 1090–2012 AD period, basing its findings on documentary evidence and instrumental records. Various documentary sources were employed for the selection of drought events, which were then interpreted at a monthly level. While the data on droughts before 1500 AD are scarce, the analysis concentrated mainly on droughts after this time. A dry year in 1501–1804 period (i.e. pre-instrumental times) was defined as a calendar year in the course of which dry patter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(154 citation statements)
references
References 36 publications
7
145
2
Order By: Relevance
“…These years have been reported and described in many studies of the area of the recent Czech Republic (e.g. Brázdil et al 2013a,b, 2015, 2016b.…”
Section: Comparison Of Spei Reconstructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These years have been reported and described in many studies of the area of the recent Czech Republic (e.g. Brázdil et al 2013a,b, 2015, 2016b.…”
Section: Comparison Of Spei Reconstructionsmentioning
confidence: 99%
“…The SPEI has been applied extensively in recent climatological and hydrological studies (e.g. Potop 2011, Heim & Brewer 2012, Li et al 2012, Paulo et al 2012, Potop et al 2012, Brázdil et al 2013a, Beguería et al 2014, Yu et al 2014, Potopová et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…However, even here, drought episodes have played an important role since the early Neolithic Age, when relatively short drought periods significantly influenced the location of early settlements (Kalis et al 2003). The dendroclimatic data and documentary sources indicate several cases of droughts with intensity not recorded during the instrumental period (Büntgen et al 2011a, Brázdil et al 2013, Cook et al 2015, Dobrovolný et al 2015. However, even the relatively short instrumental records provide a clear indication of the occurrence of persistent drought periods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most severe of these events in the last 100 yr was recorded in 1947 (Bráz dil et al 2016b this Special) with less pronounced episodes since then in 1953−1954, 1959, 1992, 2007(Bráz dil et al 2015b) and most recently in 2011−2012 (Zahradní<ek et al 2015) and 2015. Recent drought episodes after 2000 led to increased research efforts focusing on drought climatology, causes and impacts , Škvarenina et al 2009, Brázdil et al 2013, Potop et al 2014, Bochní<ek et al 2015. In the case of Austria, drought studies have focused on alpine hydrology, drought impacts on agriculture and hydrological factors such as runoff and groundwater tables (Blaschke et al 2011, Thaler et al 2012, van Loon et al 2015 but have not assessed the trends in drought indicators.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to strong winds and snow storms, Chadt (1908), Kruml (1960) and Brázdil et al (2004) also found biotic disturbance factors (Ips typographus L.) in the region in the past. Strong wind events originate mainly in connection with convective storms that generally occur during the summer half-year (April to September) or in the form of gales along conspicuous horizontal pressure gradients that usually occur during the winter half-year (October to March, Dobrovolný and Brázdil, 2003); tornadoes as well as tropical cyclones are generally absent in Central Europe (but see Setvák et al, 2003).…”
Section: P šAmonil Et Al: Disturbances Can Control Fine-scale Pedodmentioning
confidence: 99%